Social networkers and careerists: Explaining high-intensity activism among British party members. Issue 2 (March 2020) - Webb, Paul; Bale, Tim; Poletti, Monica
Drawing on survey data on the members of six British parties gathered in the immediate aftermath of the general election of 2015, this article asks what motivates members to engage in high-intensity election campaign activism. It argues that two factors are especially prominent: the aspiration to pursue a career in politics (which only accounts for a small minority of these activists) and becoming integrated into a local social network (which accounts for a much larger proportion). By contrast, members who lack either of these characteristics, but are mainly motivated to join by ideological impulses, largely restrict themselves to low-intensity activity. These findings are likely to be especially pertinent to countries with single-member district electoral systems.